Dyssynchronous Ventricular Activation in Asymptomatic Wolff-Parkinson-White Syndrome: A Risk Factor for Development of Dilated Cardiomyopathy - Udink ten Cate, Floris EA (Indian Heart Rhythm Society, 2010)
A subset of children and adults with Wolff-Parkinson-White (WPW) syndrome develop dilated cardiomyopathy (DCM). Although DCM may occur in symptomatic WPW patients with sustained tachyarrhythmias, emerging evidence suggests that significant left ventricular dysfunction may arise in WPW in the absence of incessant tachyarrhythmias. An invariable electrophysiological feature in this non-tachyarrhythmia type of DCM is the presence of a right-sided septal or paraseptal accessory pathway. It is thought that premature ventricular activation over these accessory pathways induces septal wall motion abnormalities and ventricular dyssynchrony. LV dyssynchrony induces cellular and structural ventricular remodelling, which may have detrimental effects on cardiac performance. This review summarizes recent evidence for development of DCM in asymptomatic patients with WPW, discusses its pathogenesis, clinical presentation, management and treatment. The prognosis of accessory pathway-induced DCM is excellent. LV dysfunction reverses following catheter ablation of the accessory pathway, suggesting an association between DCM and ventricular preexcitation. Accessory pathway-induced DCM should be suspected in all patients presenting with heart failure and overt ventricular preexcitation, in whom no cause for their DCM can be found.